2015
DOI: 10.1521/bumc.2015.79.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dynamic nature of “us”: An integrative approach to relationship cognition

Abstract: Most psychiatric disorders are associated with problems in interpersonal relationships. This is not surprising because people's relationships with others are an influential and integral component of their lives. The cognitive representations of these relationships can be important in understanding these relationships, and both the attachment and relational schema approaches have helped to better understand the nature of these cognitions. The attachment approach is widely researched and established, but it stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…One key line of research has focused on the component of perceived support availability, which has strong associations with health outcomes (Cohen et al, 2001;Uchino, 2009aUchino, , 2009b. This component involves a person's script for typical supportive interactions (Brunson et al, 2015;Lakey & Cohen, 2000;Pierce et al, 1997) and is typically conceptualized as a unidimensional construct with support availability versus unavailability as opposite poles of a single dimension (Goodenow et al, 1990;Williamson & O'Hara, 2017).…”
Section: Components Of Perceived Supportmentioning
confidence: 99%
“…One key line of research has focused on the component of perceived support availability, which has strong associations with health outcomes (Cohen et al, 2001;Uchino, 2009aUchino, , 2009b. This component involves a person's script for typical supportive interactions (Brunson et al, 2015;Lakey & Cohen, 2000;Pierce et al, 1997) and is typically conceptualized as a unidimensional construct with support availability versus unavailability as opposite poles of a single dimension (Goodenow et al, 1990;Williamson & O'Hara, 2017).…”
Section: Components Of Perceived Supportmentioning
confidence: 99%
“…Perceived interactions should be empirically distinct from both structural support and perceived support schema. Whereas perceived interactions pertain to memories of specific events, structural support pertains to the size and structure of one's social network, and support schema pertains to general expectations of available social resources and judgments about what is typically expected in one's life (Brunson, Acitelli, & Sharp, 2015; Cohen, Gottlieb, & Underwood, 2001). Notably, because support availability and unavailability are logically presumed to be mutually exclusive, conceptualizations of perceived support schema do not typically include a specific, separate dimension pertaining to negative perceptions (Williamson & O'Hara, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, past studies have revealed that the usage of "we" words is linked with a couple's shared identity and cognitive interdependence (Slatcher, 2009). Hence, "we" words mark a person's relational perspective and serve as a proxy for relationship awareness (Bazarova, Taft, Choi, & Cosley, 2012;Brunson, Acitelli, & Sharp, 2015); the higher the frequency of use of "we" words, the greater one's relationship awareness.…”
Section: Relationship Talkingmentioning
confidence: 99%